A bibliometric analysis study on Chlamydia trachomatis - Esra Gürbüz; Mehmet Çelik; Sevil Alkan; Serhat Karaayvaz (National Scientific Medical Center, 2023)
Aim: Chlamydia trachomatis, is one of the most important sexually transmitted disease (STD) pathogens on a global scale. In this study we aimed to analyze the publication developments with bibliometric methods on C.trachomatis by examining the research articles published between January 1970-December 2021. Material and methods: Herein, a bibliometric design was used to achieve the developments in C. trachomatis research. Research articles published in the Web of Science (WoS) database between January, 1970-December, 2021 were included in the study. The keywords selected for the search were 'Chlamydia trachomatis, Chlamydia, and C. trachomatis'. Results: The search of the WoS database for C. trachomatis research articles from 1970 to 2021 yielded 8133 results. Of the documents, 5696 were articles. 95.769% were published in Science Citation Index Expanded (SCI-EXPANDED) indexed journals. Most were published in English (94.803%). The articles were mostly from the Infectious Diseases (33.251%) research area. Most of the articles were from the USA. About 51% of the studies had funding organizations, with the United States Department of Health and Human Services provided the most financial support. Most of the articles (n=346, 6.074%) were published in the Journal of Sexually Transmitted Diseases. Although the number of publications seems to be irregular, it has not fallen below 80 articles per year, especially since 1980. The articles were cited 147,672 times (25.93 times per article) and the H-index was 133. Conclusion: STDs are still an important public health problem in almost all parts of the world. We have found that the number of published articles and citations to articles on C. trachomatis has increased rapidly, especially in recent years. However, although the number of publications in developed countries has increased, the number of publications in developing and underdeveloped countries is below the expected level. Since C. trachomatis is a global public health problem, countries with a lower number of publications should be supported financially.